Pengaruh Kualitas Pelayanan Pajak Bumi dan Bangunan Terhadap Kepuasan Konsumen di Badan Pendapatan Daerah Kabupaten Sikka The Influence of Land and Building Tax Service Quality on Consumer Satisfaction at the Sikka Regency Regional Revenue Agency - Arnoldus, Yoseph Reo; Supriyadi, Muhammad; Sari, Eliza Oktaliana (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2024)
Many people complain about several problems related to tax services at the Sikka Regency Regional Revenue Agency. Therefore, this research was carried out with the aim of finding out the influence of the quality of land and building tax services on consumer satisfaction at the Sikka Regency Regional Revenue Agency.This research uses quantitative methods, data collection was carried out by distributing questionnaires to 100 respondents who were residents of Sikka Regency. The data analysis method used in this research is multiple linear regression test, t test, coefficient of determination and F test.Based on the results of the hypothesis test, it was concluded that all Tangibles, Responsiveness, Assurance, Empathy and Reliability variables had a significant effect on consumer satisfaction at the Sikka Regency Regional Revenue Agency. Likewise, the results of the F test show that the variables Tangible, Responsiveness, Assurance, Empathy and Reliability simultaneously have a significant effect on consumersatisfaction at the Sikka Regency Regional Revenue Agency